Proton dose calculation on scatter‐corrected CBCT image: Feasibility study for adaptive proton therapy. Issue 8 (2nd July 2015) - Park, Yang‐Kyun; Sharp, Gregory C.; Phillips, Justin; Winey, Brian A.
Abstract : Purpose: To demonstrate the feasibility of proton dose calculation on scatter‐corrected cone‐beam computed tomographic (CBCT) images for the purpose of adaptive proton therapy. Methods: CBCT projection images were acquired from anthropomorphic phantoms and a prostate patient using an on‐board imaging system of an Elekta infinity linear accelerator. Two previously introduced techniques were used to correct the scattered x‐rays in the raw projection images: uniform scatter correction (CBCTus ) and a priori CT‐based scatter correction (CBCTap ). CBCT images were reconstructed using a standard FDK algorithm and GPU‐based reconstruction toolkit. Soft tissue ROI‐based HU shifting was used to improve HU accuracy of the uncorrected CBCT images and CBCTus, while no HU change was applied to the CBCTap . The degree of equivalence of the corrected CBCT images with respect to the reference CT image (CTref ) was evaluated by using angular profiles of water equivalent path length (WEPL) and passively scattered proton treatment plans. The CBCTap was further evaluated in more realistic scenarios such as rectal filling and weight loss to assess the effect of mismatched prior information on the corrected images. Results: The uncorrected CBCT and CBCTus images demonstrated substantial WEPL discrepancies (7.3 ± 5.3 mm and 11.1 ± 6.6 mm, respectively) with respect to the CTref, while the CBCTap images showed substantially reduced WEPL errors (2.4 ± 2.0 mm). Similarly, the CBCTap ‐based treatment plans demonstrated a high pass rate (96.0% ± 2.5% in 2 mm/2% criteria) in a 3D gamma analysis. Conclusions: A priori CT‐based scatter correction technique was shown to be promising for adaptive proton therapy, as it achieved equivalent proton dose distributions and water equivalent path lengths compared to those of a reference CT in a selection of anthropomorphic phantoms.